An integrated, cross-regulation pathway model involving activating/adaptive and feed-forward/feed-back loops for directed oscillatory cAMP signal-relay/response during the development of Dictyostelium - Jaiswal, Pundrik; Meena, Netra Pal; Chang, Fu-Sheng; Liao, Xin-Hua; Kim, Lou; Kimmel, Alan R. (Frontiers in Cell and Developmental Biology, 2024)
Self-organized and excitable signaling activities play important roles in a wide range of cellular functions in eukaryotic and prokaryotic cells. Cells require signaling networks to communicate amongst themselves, but also for response to environmental cues. Such signals involve complex spatial and temporal loops that may propagate as oscillations or waves. When Dictyostelium become starved for nutrients, cells within a localized space begin to secrete cAMP. Starved cells also become chemotactic to cAMP. cAMP signals propagate as outwardly moving waves that oscillate at ~6 min intervals, which creates a focused territorial region for centralized cell aggregation. Proximal cells move inwardly toward the cAMP source and relay cAMP outwardly to recruit additional cells. To ensure directed inward movement and outward cAMP relay, cells go through adapted and de-adapted states for both cAMP synthesis/degradation and for directional cell movement. Although many immediate components that regulate cAMP signaling (including receptors, G proteins, an adenylyl cyclase, phosphodiesterases, and protein kinases) are known, others are only inferred. Here, using biochemical experiments coupled with gene inactivation studies, we model an integrated large, multi-component kinetic pathway involving activation, inactivation (adaptation), re-activation (resensitization), feed-forward, and feed-back controls to generate developmental cAMP oscillations.